Percutaneous transhepatic embolization of gastro-esophageal varices for the treatment of variceal bleeding in portal vein thrombosis secondary to hepatocellular carcinoma: A case report - Amol S. Rathod; Pankaj Banode (Radiology Case Reports)
Percutaneous transhepatic embolization (PTE) is a minimally invasive and effective intervention for managing refractory variceal bleeding in patients with portal vein thrombosis (PVT) secondary to hepatocellular carcinoma (HCC). This case report highlights the successful application of PTE in a 69-year-old nonalcoholic male with chronic liver disease and HCC. The patient, previously treated with transarterial chemoembolization (TACE) for segment VIII HCC, presented recurrent hematemesis and significant anemia despite prior endoscopic esophageal variceal band ligation. Diagnostic imaging revealed portal vein thrombosis and extensive gastro-esophageal varices. Given the patient's unresponsiveness to conventional endoscopic treatments, an emergency PTE was performed. Using a percutaneous transhepatic approach, the left portal vein was accessed under real-time ultrasound guidance. Subsequent venography confirmed extensive varices draining into the splenic artery. Embolization involved deploying a combination of pushable coils and a 20% glue solution, which achieved complete obliteration of the varices, as confirmed by nonprocedure imaging. The track from the liver surface to the left portal vein was sealed using a glue-lipiodol mixture to prevent complications. The patient demonstrated significant clinical improvement postprocedure, with no further episodes of hematemesis. Hemoglobin levels stabilized following transfusion of packed red cells, and the patient was discharged in stable condition. This case underscores the role of PTE as a safe and effective salvage therapy for refractory variceal bleeding in complex cases involving PVT secondary to HCC.